A network perspective on organizational learning research in tourism and hospitality: A systematic literature review. Issue 7 (8th July 2019) - Binder, Petra
Abstract : Purpose: The purpose of this paper is to review existing literature on organizational learning (OL) through networking activities in tourism and hospitality (T&H) research. Referring to theories and concepts from the mainstream literature in OL and inter-organizational network research, the study provides an overview of the existing level of knowledge in T&H research, elaborates theoretical and practical implications and suggests future research directions. Design/methodology/approach: A systematic literature review approach was used to identify and analyze relevant literature. The literature search involved six scientific online databases, namely, EBSCOhost, Emerald, ProQuest, Sage, ScienceDirect and Web of Knowledge, which were systematically scanned with defined keywords. Relevant articles were evaluated, selected, analyzed and synthesized to find out what is already known and what is yet to be known. Findings: A total of 69 articles were identified that present insights into OL through networking activities in T&H research. The review reveals that the resource, and especially the knowledge-based view of the firm, social capital theory, the relational view and trust and agglomeration theory represent insightful theoretical approaches to study OL phenomena and OL outcomes such as innovation, value creation and competitive advantage. Originality/value: According to the author's information, this paper represents the first attempt to provide a comprehensive review of T&H-specific OL literature from a network perspective. The findings call for increased attention to this research field, especially regarding the adaptation of OL concepts to a T&H-specific context as a networked industry.